2017
DOI: 10.1096/fj.201600713r
|View full text |Cite
|
Sign up to set email alerts
|

Autophagosomes cooperate in the degradation of intracellular C‐terminal fragments of the amyloid precursor protein via the MVB/lysosomal pathway

Abstract: Brain regions affected by Alzheimer disease (AD) display well‐recognized early neuropathologic features in the endolysosomal and autophagy systems of neurons, including enlargement of endosomal compartments, progressive accumulation of autophagic vacuoles, and lysosomal dysfunction. Although the primary causes of these disturbances are still under investigation, a growing body of evidence suggests that the amyloid precursor protein (APP) intracellular C‐terminal fragment β (C99), generated by cleavage of APP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 74 publications
9
43
0
Order By: Relevance
“…Treatments with CQ or Baf A1 inhibited β-CTFs degradation and reduced Aβ peptides and sAPPβ production while they increased sAPPα secretion, suggesting that the amyloidogenic pathway was reduced in favour of the α-secretase cleavage. These results are in agreement with previous reports showing that the endosomal/lysosomal pathway is of particular importance for the whole APP processing, and in particular for efficient amyloidogenic processing [14,15,17].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Treatments with CQ or Baf A1 inhibited β-CTFs degradation and reduced Aβ peptides and sAPPβ production while they increased sAPPα secretion, suggesting that the amyloidogenic pathway was reduced in favour of the α-secretase cleavage. These results are in agreement with previous reports showing that the endosomal/lysosomal pathway is of particular importance for the whole APP processing, and in particular for efficient amyloidogenic processing [14,15,17].…”
Section: Resultssupporting
confidence: 93%
“…These intriguing questions remain open and require further investigations. Our results also confirmed that besides being cleaved by γ-secretase, APP-CTFs are efficiently degraded by the endosomal/lysosomal pathway, as it was previously reported [14,15,17]. Along with reducing APP-CTFs degradation, drugs that were used to inhibit the endosomal/lysosomal pathway significantly reduced the secretion of Aβ peptides and sAPPβ species.…”
Section: Discussionsupporting
confidence: 91%
“…A recent report by González et al . (74) has demonstrated a relationship between the endolysosomal degradation pathway and autophagy on the proteolytic processing and turnover of amyloid precursor protein. The authors demonstrated that inhibition of autophagosome formation leads to its massive accumulation in intracellular vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of M pro is regulated over mechanisms comprising maturation from the polyprotein by autoprocessing of nsp4-5 and nsp5-6, as well as concentration and substrate induced self-assembly into an active dimeric unit [12][13][14]. After freeing itself, M pro liberates nsp's 6-16 from the polyprotein by specifically targeting their nsp inter-domain junctions.…”
Section: Introductionmentioning
confidence: 99%